An open trial of mindfulness‐based stress reduction for young adults with social anxiety disorder. Issue 1 (8th December 2016) - Hjeltnes, Aslak; Molde, Helge; Schanche, Elisabeth; Vøllestad, Jon; Lillebostad Svendsen, Julie; Moltu, Christian; Binder, Per‐Einar
Abstract : The present study investigated mindfulness‐based stress reduction (MBSR) for young adults with a social anxiety disorder (SAD) in an open trial. Fifty‐three young adults in a higher education setting underwent a standard eight‐week MBSR program. Eight participants (15%) did not complete the program. Participants reported significant reductions in SAD symptoms and global psychological distress, as well as increases in mindfulness, self‐compassion, and self‐esteem. Using intention‐to‐treat (ITT) analyses, effect sizes ranged from large to moderate for SAD symptoms (Cohen's d = 0.80) and global psychological distress ( d = 0.61). Completer analyses yielded large effect sizes for SAD symptoms ( d = 0.96) and global psychological distress ( d = 0.81). The largest effect sizes were found for self‐compassion ( d = 1.49) and mindfulness ( d = 1.35). Two thirds of the participants who were in the clinical range at pretreatment reported either clinically significant change (37%) or reliable improvement (31%) on SAD symptoms after completing the MBSR program, and almost two thirds reported either clinically significant change (37%) or reliable improvement (26%) on global psychological distress. MBSR may be a beneficial intervention for young adults in higher education with SAD, and there is a need for more research on mindfulness and acceptance‐based interventions for SAD.